THE INFLUENCE OF POLITICAL MONEY ON IRAQ'S POLITICAL PROCESS: A DEEP DIVE - Hussein, Kamal Razaq (Journal of Social Science, 2025)
Objective: The current study aims to identify the important factors that contribute to the flow of political money in Iraq. Method: For this purpose, a method approach was used. A questionnaire was developed for quantitative analysis, and face-to-face interviews were conducted for qualitative analysis. Regression analysis and descriptive statistics were employed for quantitative data analysis, and for qualitative data, thematic analysis was done. Results: The findings from the quantitative data set suggest that political money somewhat correlates with corruption, except for the foreign corporate influence. Similarly, the result of thematic analysis highlights the key themes, which suggests a more positive correlation between the variables. Novelty: The study recommends implementing stronger oversight mechanisms, promoting transparency and addressing the influence of the external political actors in Iraq’s political and economic areas to enhance stability and equitable governance.